Kingdom of Lesotho : First Review Under the Three-Year Extended Credit Facility Arrangement and Requests for Waiver of Nonobservance of Performance Criterion and Modification of Performance Criteria-Staff Report and Press Release. (IMF Staff Country Reports; Country Report ;, 2011)
The authorities reiterated their firm commitment to the policies and objectives outlined in the May 17, 2010 Memorandum of Economic and Financial Policies. They are committed to a reduction in other primary spending by 2 percentage points of GDP. With the medium-term outlook broadly unchanged, the policy discussions focused on the FY2011-12 budget and the authorities' structural reform agenda. Revenues are projected to fall in 2011-12, reflecting the disappearance of exceptional receipts in 2010-11. On the spending side, the authorities are facing a number of additional commitments-some of which are of a temporary nature.